A clinical trial comparing BiVap (Richard Wolf®) saline vaporization of the prostate vs. TwisterTM Diode Laser System in the treatment of benign prostatic obstruction between prostate volume 90 to 150 ml. Issue 1 (February 2022) - Karakose, Ayhan; Yitgin, Yasin
Introduction: To evaluate the efficacy, safety and postoperative outcomes of the BiVap and Twister systems with benign prostatic obstruction (BPO) in prostate volüm between 90–150 ml. Methods: In total, we included 131 patients treated with BiVap system (n = 68) and Twister system (n = 63). Postoperative complications including urinary tract infection, transient hematuria, severe dysuria and fever >38° C, urinary incontinence and urethral stricture were also noted. All patients were evaluated at the postoperative 1st, 3rd, 6th and 12th month and preoperative and postoperative values of IPSS score, QoL score, total PSA, IIEF 15, PVR, Qmax and Qave were compared. Results: Preoperative demographic characteristics were similar in the 2 groups. There was observed significant improvement for IPSS, Qmax, Qave, PVR, and QoL score by the postoperative first month compared to the preoperative values in both groups. Maximum improvement in the IPSS, Qmax, Qave, QoL score and PVR were achieved at postoperative 6, 3, 12, 3 and 12th months respectively in group 1. In group 2 maximum improvement in the same parameters were achieved at postoperative 6, 3, 6, 6 and 12th months, respectively. Conclusions: BiVap and Twister systems are safe, effective, and useful technique, which can be used in the surgical treatment of BPO between 90–150 ml.